PELAKSANAAN TUGAS PENDAMPINGAN DESA DIDESA DELUK KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2015-2016 - Alpisyahrin, Ryan; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study relates to the Village based on Law No. 6 of 2014 concerning Villages, then based on Government Regulation No. 43 of 2014 concerning the implementation of Law No. 6 of 2014 the implementation of village escort duties in Deluk Village Bantan District, Bengkalis Regency based on Ministerial Regulation Village No. 3 of 2015 concerning Village assistance, as an activity to carry out community empowerment actions through village assessment, organization, direction and facilitation. This study discusses how the implementation of mentoring tasks in Deluk Village, Bantan District, Bengkalis Regency in 2015-2016, what are the inhibiting factors Village assistants in carrying out community empowerment programs, the purpose of this study is to find out the implementation of mentoring tasks in the Village of Deluk, Bantan Sub-District, Bengkalis Regency in 2015-2016, to determine the inhibiting factors of village assistance in carrying out community empowerment programs. This type of research is qualitative, to describe the real conditions in the field systematically and accurately related to the field based on certain facts (information). The method of data collection is done by interview, documentation, and observation in the field. The results of the study explained that the village bureaucracy in the Delux Village was quite clear regarding the task of implementation both for the PLD (Village Local Companion) through the SOP (Standard Operating Procedure) from the Center and Village Facilitators from the District through the Technical Guidelines, in terms of fieldwork there are Village facilitators who are not optimal in carrying out their duties. For communication Village Facilitators in Desa Deluk have coordinated well which can be seen from the attendance of the coordination meetings conducted. For Village Assistance Resources, they have understood the main tasks and functions, but specifically for PLD, they have not played an optimal role in the Village. Factors that can be a barrier to Village facilitators in carrying out their tasks are the lack of support from the community and the Village Government and the quality and quantity of Village Facilitators themselves. Keywords: Implementation, Village assistance, Village companion